2018
DOI: 10.1016/j.peptides.2017.12.025
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced angiotensin II induced sodium appetite in renovascular hypertensive rats

Abstract: Renovascular hypertensive 2-kidney, 1-clip (2K1C) rats have an increased activity of the renin-angiotensin system and an initial transitory increase in daily water and NaCl intake. However, the dipsogenic and natriorexigenic responses to angiotensin II (ANG II) have not been tested yet in 2K1C rats. Therefore, in the present study, we evaluated water and 0.3 M NaCl intake induced by water deprivation (WD)-partial rehydration (PR) or intracerebroventricular (icv) ANG II in 2K1C rats. In addition, the cardiovasc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 40 publications
1
14
0
Order By: Relevance
“…A number of previous studies have shown that the brain RAS is involved in stimulation of sodium intake and that actions of RAS components, especially ANG II, in the SFO and lamina terminalis (2,5,25,29,44). We recently showed that the PRR is a functional component of the brain RAS that mediates ANG II formation and regulates other RAS components (1).…”
Section: Discussionmentioning
confidence: 99%
“…A number of previous studies have shown that the brain RAS is involved in stimulation of sodium intake and that actions of RAS components, especially ANG II, in the SFO and lamina terminalis (2,5,25,29,44). We recently showed that the PRR is a functional component of the brain RAS that mediates ANG II formation and regulates other RAS components (1).…”
Section: Discussionmentioning
confidence: 99%
“…Dietary sodium deprivation elicits a strong salt appetite in rats, 86 as does bilateral adrenalectomy, 87,88 aldosterone via its actions on the brain, 89,90 and hypovolaemic stimuli. [94][95][96][97][98] However, sodium intake is not always stimulated when hypovolaemia is present or when blood angiotensin II levels are elevated. [94][95][96][97][98] However, sodium intake is not always stimulated when hypovolaemia is present or when blood angiotensin II levels are elevated.…”
Section: Salt Appetitementioning
confidence: 99%
“…[91][92][93] The AV3V region is strongly implicated in salt appetite, in part via central angiotensin II pathways from the subfornical organ. [94][95][96][97][98] However, sodium intake is not always stimulated when hypovolaemia is present or when blood angiotensin II levels are elevated.…”
Section: Salt Appetitementioning
confidence: 99%
“…Finally, Fos expression in the MnPO/OVLT located in the forebrain, in the iNTS, and in the brain stem increased in WD 2K1C rats, and further increased after 2 h of rehydration. Many studies have shown the importance of ANG II for water intake and sodium appetite (Sato et al, 1996;McKinley and Johnson, 2004;McKinley et al, 2015;Roncari et al, 2018). WD induces increased plasma osmolarity and renin levels that promote thirst and sodium appetite (Sato et al, 1996;De Luca Jr et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Renovascular hypertension is a type of secondary hypertension caused mainly by atherosclerotic renal artery stenosis, followed by fibromuscular disease, arteritis, thrombosis, arterial dissection, and stenosis in a transplanted kidney [reviewed in ( Derkx and Schalekamp, 1994 ; Textor, 2017 ; Herrmann and Textor, 2018 )], and account for approximately 5–6% of high blood pressure cases in the elderly ( Hansen et al, 2002 ). The increase in renin–angiotensin–aldosterone system (RAAS) activity has a pivotal role in the development of renovascular hypertension ( Leenen et al, 1975 ; Lincevicius et al, 2015 ; Textor, 2017 ; Roncari et al, 2018 ). In fact, the central or peripheral administration of AT1 receptor or aldosterone receptor antagonist was efficient in decreasing the high blood pressure levels of renovascular hypertension similar to that in 2-kidney-1clip (2K1C) rats ( Wilcox et al, 1996 ; de Oliveira-Sales et al, 2010 ; Lincevicius et al, 2015 ; Boshra and Abbas, 2017 ).…”
Section: Introductionmentioning
confidence: 99%